Proteasome and Neurodegenerative Diseases - (:unkn) unknown (ELSEVIER ACADEMIC PRESS INC, 2012)
Proteasomal degradation of damaged proteins is involved in the pathogenesis of many neurodegenerative diseases including Alzheimer's, Parkinson's, Huntington's, stroke, and amyotrophic lateral sclerosis. A malfunction of the proteasomal activity may be the result or the consequence of protein aggregation, which is a key process for most neurodegenerative diseases. Because of the widespread aspects of the proteasomal involvement in the progression of these diseases, many studies are focused on this research.
Keywords: AMYOTROPHIC-LATERAL-SCLEROSIS; OXIDATIVELY MODIFIED PROTEINS; NEURONAL INTRANUCLEAR INCLUSIONS; SUPEROXIDE-DISMUTASE PROTEINS; ALPHA-SYNUCLEIN AGGREGATION; G93A-SOD1 TRANSGENIC MICE; AMYLOID-BETA-PROTEIN; ALZHEIMERS-DISEASE; PARKINSONS-DISEASE; LIPID-PEROXIDATION